"Every coin has two sides": The effects of dialectical thinking and attitudinal ambivalence on psychological discomfort and consumer choice. Issue 2 (11th October 2016) - Pang, Jun; Keh, Hean Tat; Li, Xiuping; Maheswaran, Durairaj
Abstract: Prior research suggests that consumers experience psychological discomfort when they make a choice under attitudinal ambivalence. The research reported here examines systematic cross‐cultural variations in psychological discomfort as a function of dialectical thinking and attitudinal ambivalence in the context of choice. It shows that compared to nondialectical (Western) consumers, dialectical (Eastern) consumers experience less psychological discomfort when they hold bivalent evaluations of the focal object, but more psychological discomfort when they hold univalent evaluations (Study 1). It also identifies "uncertainty about making the correct choice" as the underlying process that accounts for these findings (Study 2). In addition, this research explores the downstream effects of psychological discomfort on choice deferral in the context of free choice (Study 3) and preference reversal in the context of forced choice (Study 4). Contributions to and implications for research on attitudinal ambivalence, choice behavior, and dialectical thinking are discussed.